2016
DOI: 10.2215/cjn.02110215
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Neurocognition in Youth with CKD Using a Novel Computerized Neurocognitive Battery

Abstract: Background and objectives Neurocognitive problems in CKD are well documented; time-efficient methods are needed to assess neurocognition in this population. We performed the first study of the efficient 1-hour Penn Computerized Neurocognitive Battery (CNB) in children and young adults with CKD.Design, setting, participants, & measurements We administered the Penn CNB cross-sectionally to individuals aged 8-25 years with stage 2-5 CKD (n=92, enrolled from three academic nephrology practices from 2011 to 2014) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 35 publications
2
19
1
Order By: Relevance
“…Some have found no significant differences in memory (verbal and nonverbal) between children with and without CKD (11). Others have reported specific deficits in complex auditory attention, verbal working memory, and the recognition of emotional states (11,12). The extent and patterns of neurocognitive and academic impairment in children may also vary by CKD stage.…”
Section: Introductionmentioning
confidence: 99%
“…Some have found no significant differences in memory (verbal and nonverbal) between children with and without CKD (11). Others have reported specific deficits in complex auditory attention, verbal working memory, and the recognition of emotional states (11,12). The extent and patterns of neurocognitive and academic impairment in children may also vary by CKD stage.…”
Section: Introductionmentioning
confidence: 99%
“…However, the association between cognitive impairment and CKD persists (7)(8)(9), even after adjusting for cerebrovascular diseases (1)(2)(3). Moreover, cognitive impairment has been observed in children with CKD, the large majority of whom do not have cerebrovascular disease (10). Most importantly, several studies showed that cognitive function improved and sometimes almost normalized after kidney transplantation (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Research into the neuropsychological profile of children post‐kidney transplantation shows lower performance on complex auditory attention and visual working memory tasks . Performance on continuous performance tasks used to directly assess attention and inhibitory control has been found to be significantly impaired among youth with chronic kidney disease . Longer duration of chronic kidney disease is associated with increased risk of poor performance on this measure of attention .…”
Section: Introductionmentioning
confidence: 99%
“…8 Performance on continuous performance tasks used to directly assess attention and inhibitory control has been found to be significantly impaired among youth with chronic kidney disease. 18,19 Longer duration of chronic kidney disease is associated with increased risk of poor performance on this measure of attention. 20 Parents of children with chronic kidney disease rate their children as having more difficulties with working memory, planning, and organizing skills than do parents of children without chronic kidney disease.…”
Section: Introductionmentioning
confidence: 99%